The CD40/CD40 Ligand Interaction Is Required for Resistance to Toxoplasmic Encephalitis - Reichmann, Gaby (American Society for Microbiology, 2000)
Since the CD40/CD40 ligand (CD40L) interaction is involved in the regulation of macrophage production of interleukin 12 (IL-12) and T-cell production of gamma interferon (IFN-γ), effector cell functions associated with resistance to Toxoplasma gondii, the role of CD40L in immunity to this parasite was assessed. Infection of C57BL/6 mice with T. gondii results in an upregulation of CD40 expression on accessory cell populations at local sites of infection as well as in lymphoid tissues. Splenocytes from C57BL/6 mice infected with T. gondii for 5 days produced high levels of IL-12 and IFN-γ when stimulated with toxoplasma lysate antigen, and blocking CD40L did not significantly alter the production of IFN-γ or IL-12 by these cells. Similar results were observed with splenocytes and mononuclear cells isolated from the brains of chronically infected mice. Interestingly, although CD40L(−/−) mice infected with T. gondii produced less IL-12 than wild-type mice, they produced comparable levels of IFN-γ but succumbed to toxoplasmic encephalitis 4 to 5 weeks after infection. The inability of CD40L(−/−) mice to control parasite replication in the brain correlated with the ability of soluble CD40L, in combination with IFN-γ, to activate macrophages in vitro to control replication of T. gondii. Together, these results identify an important role for the CD40/CD40L interaction in resistance to T. gondii. However, this interaction may be more important in the control of parasite replication in the brain rather than the generation of protective T-cell responses during toxoplasmosis.